Math, asked by ankitraj7, 1 year ago

solve it plz plz i dont solbe it its i viery hard for me so ppz solve it

Attachments:

Answers

Answered by hardiksharmah10
1
 2^{(-1)} = \frac{1}{2} \\ \\ 3^{(-1)} = \frac{1}{3} \\ \\ (2^{(-1)} - 3^{(-1)} )^{(-1)} = (\frac{1}{2} - \frac{1}{3} )^ {(-1)} = ( \frac{1}{6} )^{(-1)} = 6

 ( 6^{(-1)}  - 8^{(-1)} )^{(-1)} =  (\frac{1}{6}  - \frac{1}{8})^{(-1)} = ( \frac{1}{24} )^{(-1)} = 24

Now 6 + 24 = 30.

Please mark as Brainliest if you got it.




ankitraj7: thnkx
ankitraj7: it is wrong answer
hardiksharmah10: iT IS NOT WRONG
Shaurya181: no it is correct i am sure
Answered by Shaurya181
1
Answer is this..... .....
Attachments:

ankitraj7: thnkx
Similar questions